Factoring with Pell conics - Šleževičienė, Rasa (Lietuvos matematikos rinkinys, 2004)
In the paper the Pell conics method for factoring integers, based on observations of Lemmermeyer [2, 3], is presented explicitly. Moreover, a similar algorithm for factoring polynomials over finite fields is given.
Keywords: factoring; Pell conics